If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(f + -4) + 3(d + -6) = 0 Reorder the terms: 2(-4 + f) + 3(d + -6) = 0 (-4 * 2 + f * 2) + 3(d + -6) = 0 (-8 + 2f) + 3(d + -6) = 0 Reorder the terms: -8 + 2f + 3(-6 + d) = 0 -8 + 2f + (-6 * 3 + d * 3) = 0 -8 + 2f + (-18 + 3d) = 0 Reorder the terms: -8 + -18 + 3d + 2f = 0 Combine like terms: -8 + -18 = -26 -26 + 3d + 2f = 0 Solving -26 + 3d + 2f = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 3d + 26 + 2f = 0 + 26 Reorder the terms: -26 + 26 + 3d + 2f = 0 + 26 Combine like terms: -26 + 26 = 0 0 + 3d + 2f = 0 + 26 3d + 2f = 0 + 26 Combine like terms: 0 + 26 = 26 3d + 2f = 26 Add '-2f' to each side of the equation. 3d + 2f + -2f = 26 + -2f Combine like terms: 2f + -2f = 0 3d + 0 = 26 + -2f 3d = 26 + -2f Divide each side by '3'. d = 8.666666667 + -0.6666666667f Simplifying d = 8.666666667 + -0.6666666667f
| x^3-x(6x-5)=0 | | 0=x^2-17x+72 | | 5(3p+2)-2(5p-3)= | | 2x-5(x-5)=-2+3x-9 | | 4.9x^2-20x+300=0 | | 4.9x*-20x+300=0 | | 4(2x+1)+7=7(4x-3) | | 5(q+2)+2q=1 | | -2x=-70 | | -3(x+9)=12 | | 23x-7=5 | | -4-3x=10x-6 | | 8h=16-6h | | 2d+4(3d+2)= | | 5a+3(a+4)= | | 9n-17=6n+7 | | 5(3x+4)=50 | | 2x+x+3x=6 | | -12,720+20x=0 | | 4x+(x+7)=-28-2x | | 5(x.2)=40/2 | | 1.6n=0.8n | | y=10x+4 | | 3x^4-30x^2-33=0 | | 4+2n=8n+16 | | -8+s=-56 | | 2x+y=-11 | | 7x=10x-5 | | 3.3=0.15x | | 6x+13=-17 | | 5(3p+2)-3(5p-3)= | | x+3x-5x-15= |